Kekuatan Geser Panel Kayu Vertikal Dengan Perkuatan Single Bracing Tulangan Baja Akibat Pembebanan Siklik - Monika, Fanny (Semesta Teknika, 2016)
PanelsÂ  in wooden construction serve as walls as well as providing structural lateralÂ  resistanceÂ  againstÂ  earthquakeÂ  ifÂ  designed well. Panel materialsÂ  consist of frames withÂ  sheathingsÂ  suchÂ  asÂ  PlywoodÂ  or Oriented Strand Board(OSB)Â  connectedÂ  toÂ  woodenÂ  frames with nails as connectors. Lateral force of the panels can be increased, for example by adding diagonal rods/bracings to the frames. In this study a woodenÂ  panel which was Sengon wooden panel connected to Laminated Veneer Lumber(LVL) wooden panel with CN 50 nails withÂ  a diameter of 2,8 mm andÂ  the distance betweenÂ  the nails was 240 mm with plainÂ  steelÂ  reinforcementÂ  single bracing with a diameter of 8 mm in pull position using corner plate as a connector between bracing and LVL wooden panel. CyclicÂ  test had 20%Îy,Â  40%Îy,Â  60%ÎyÂ  deformation controlsÂ  andÂ  loaded with monotonicÂ  until wooden panels collapsed. TheÂ  results of cyclicÂ  testÂ  inÂ  stableÂ  conditionÂ  60%Îy had equivalent viscous damping ratio values of 8,324%.Â  FailuresÂ  inÂ  panelsÂ  oftenÂ  happenedÂ  toÂ  connectingÂ  nails,Â  cornerÂ  plates,Â  and steelÂ  bracings. TheÂ  typesÂ  ofÂ  failure were NailÂ  Pull-ThroughÂ  ofÂ  Sheathing,Â  Pull-ThroughÂ  SheathingÂ  Failures,Â  MudsillÂ  Failure,Â  bucklingÂ  onÂ  cornerÂ  plates,Â  and buckling on steel bracingsÂ